Antibiotics with antibiofilm activity – rifampicin and beyond - Ferreira, Luís; Pos, Ema; Nogueira, Daniela Rodrigues; Ferreira, Filipa Pinto; Sousa, Ricardo; Abreu, Miguel Araújo (Frontiers in Microbiology, 2024)
The management of prosthetic joint infections is a complex and multilayered process that is additionally complicated by the formation of bacterial biofilm. Foreign material provides the ideal grounds for the development of an intricate matrix that hinders treatment and creates a difficult environment for antibiotics to act. Surgical intervention is often warranted but requires appropriate adjunctive therapy. Despite available guidelines, several aspects of antibiotic therapy with antibiofilm activity lack clear definition. Given the escalating challenges posed by antimicrobial resistance, extended treatment durations, and tolerance issues, it is essential to ensure that antimicrobials with antibiofilm activity are both potent and diverse. Evidence of biofilm-active drugs is highlighted, and alternatives to classical regimens are further discussed.